Clinical and demographic characteristics and two-year efficacy and safety data of 508 multiple sclerosis patients with fingolimod treatment - AĞAN YILDIRIM, KADRİYE (My University, 2023)
Introduction: Fingolimod is the first oral immunomodulatory treatment used as secondary care therapy in the treatment of multiple sclerosis for the last 10 years. The objective of our study is to reveal the experiences of the first generic fingolimod active ingredient treatment in different centers across Turkey. Method: The first generic fingolimod efficacy and safety data of patients followed-up in 29 different clinical multiple sclerosis units in Turkey were analyzed retrospectively. Data regarding efficacy and safety of the patients were transferred to the data system both before the treatment and on the 6th, 12th and 24th month following the treatment. The data were analyzed using the IBM SPSS 20.00. P value of <0.05 was considered to be statistically significant. Results: A total of 508 multiple sclerosis patients, 331 of whom were women, were included in the study. Upon comparing the Expanded Disability Status values before and after the treatment, a significant decrease was observed, especially at month 6 and thereafter. Since bradycardia occurred in 11 of the patients (2.3%), the first dose had to be longer than 6 hours. During the observation of the first dose, no issues that could prevent the use of the drug occured. Side effects were seen in 49 (10.3%) patients during the course of fingolimod treatment. Respectively, the most frequent side effects were bradycardia, hypotension, headache, dizziness and tachycardia. Conclusion: The observed results regarding efficacy and safety were similar to clinical trial data in the literature and real life data in terms of the first equivalent with fingolimod active ingredient.
Keywords: Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Psikiyatri; Sinirbilim ve Davranış; SİNİR BİLİMİ; Clinical Medicine (MED); Life Sciences (LIFE); PSYCHIATRY; NEUROSCIENCE & BEHAVIOR; NEUROSCIENCES; Genel Sinirbilim; Psikiyatri ve Ruh Sağlığı; General Neuroscience; Psychiatry and Mental Health; Efficacy; fingolimod; multiple sclerosis; safety; Efficacy; fingolimod; multiple sclerosis; safety